Type 2 diabetes mellitus coincident with pulmonary or latent tuberculosis results in modulation of adipocytokines - Kumar, Nathella Pavan (Cytokine, 2016)
Type 2 diabetes mellitus (T2DM) is recognized as major risk factor for the progress of active pulmonary tuberculosis (PTB), although the mechanistic link between diabetes and tuberculosis remains poorly characterized. Moreover, the influence of poorly controlled diabetes on the baseline levels of adipocytokines in the context of tuberculosis has not been explored in detail. To characterize the influence of coexistent DM on adipocytokine levels in pulmonary or latent TB (LTB), we examined circulating levels of adipocytokines in the plasma of individuals with PTB-DM or LTB-DM and compared them with those without DM (PTB or LTB). PTB-DM or LTB-DM is characterized by diminished circulating levels of adiponectin and adipsin and/or heightened circulating levels of leptin, visfatin and PAI-1. In addition, adiponectin and adipsin exhibit a significant negative correlation, whereas with leptin, visfatin and PAI-1 display a significant positive correlation with HbA1C levels and random blood glucose levels. Therefore, our data reveal that PTB-DM or LTB-DM is characterized by alterations in the systemic levels of adipocytokines, indicating that altered adipose tissue inflammation underlying Type 2 diabetes potentially contributes to pathogenesis of TB disease.